Strain Engineering of Cu2O@C2N for Enhanced Methane-to-Methanol Conversion - Shuxin Kuai; Bo Li; Jingyao Liu (Molecules)
Inspired by the active site of methane monooxygenase, we designed a Cu2O cluster anchored in the six-membered nitrogen cavity of a C2N monolayer (Cu2O@C2N) as a stable and efficient enzyme-like catalyst. Density functional theory (DFT) calculations reveal that the bridged Cu-O-Cu structure within C2N exhibits strong electronic coupling, which is favorable for methanol formation. Two competing mechanisms—the concerted and radical-rebound pathways—were systematically investigated, with the former being energetically preferred due to lower energy barriers and more stable intermediate states. Furthermore, strain engineering was employed to tune the geometric and electronic structure of the Cu-O-Cu site. Biaxial strain modulates the Cu-O-Cu bond angle, adsorption properties, and d-band center alignment, thereby selectively enhancing the concerted pathway. A volcano-like trend was observed between the applied strain and the methanol formation barrier, with 1% tensile strain yielding the overall energy barrier to methanol formation (ΔGoverall) as low as 1.31 eV. N2O effectively regenerated the active site and demonstrated strain-responsive kinetics. The electronic descriptor Δε (εd − εp) captured the structure–activity relationship, confirming the role of strain in regulating catalytic performance. This work highlights the synergy between geometric confinement and mechanical modulation, offering a rational design strategy for advanced C1 activation catalysts.